ANALYSIS OF METHODS OF FORMATION OF MEASURING SIGNALS FOR THE CONTROL OF NAVIGATION SYSTEMS AND TRAFFIC MANAGEMENT BY MARINE TRANSPORT MEANS - Дакі, О. А.; Штрибець, В. В.; Трофіменко, А. О. (Science-based technologies, 2019)
The article presents the results of the analysis of the existing methods of forming measuring signals for monitoring the technical condition of navigation systems and systems for controlling the movement of ships on the example of radio systems. The results of the analysis of measuring signal generation methods for monitoring the technical condition of navigation systems and systems for controlling marine traffic, existing methods for measuring signals synthesis, allowed determining their shortcomings and substantiating the scientific problem of controlling the technical condition of navigation systems and systems for controlling marine traffic during actual condition. The necessity of implementation for determining the technical condition of navigation systems and complexes and controlling the movement of sea vessels of means of synthesizing polyharmonic measuring signals with improved characteristics is substantiated. Among certain advantages from using such signals, the most significant are a significant reduction in the time allotted for measuring parameters, increasing the calibration interval, improving the accuracy of reproducing a waveform, improving noise immunity and determining the parameters of special-purpose radio systems that are monitored their technical condition. The results of the work will allow solving the scientific problem of ensuring the reliability of control of the technical condition of navigation systems and systems and control of the movement of sea vessels with optimal temporal characteristics to ensure the timeliness and efficiency of determining possible failures during their operation and maintenance according to the actual condition. Therefore, it is proposed to use polyharmonic measuring signals to automate the process of monitoring the technical condition of navigation systems and systems for controlling the movement of marine transport means.